Թյուրքալեզու ցեղերի վաղ պատմության ուսումնասիրության աղբյուրները - Շ. Ս. Այվազյան (ՀՀ ԳԱԱ հրատ.)
Сведения по истории тюркоязычных народов можно почерпнуть из греко-римских, армянских, арабских и других источников. Сочинения таких авторов, как Гекатей Милетийский, Страбон, Геродот, М. Хоренаци, М. Дасхуранци, A. Ластиверци проливают свет на ранний период истории тюркоязычных народов. When studying any problem related to Turkic speaking peoples’ origins, culture, or history, we should use different sources, where we can find any direct or indirect information about them. There are many written Greek, Roman, Armenian, Arabic,and other sources that inform us about Central Asia, Far, and Middle East and their inhabitants from ancient times until now. The works by such authors as Hecateus, Strabo, Herodotus, the Armenian authors M. Khorenatsi, M. Daskhurantsi, A.Lastivertsi and others are very important for the Turkic speaking peoples’ early history.
Keywords: History; Geography; Anthropology; Recreation; Philology; Linguistics; Language and Literature; D History; GEC Ethnic Groups and Races